THE CORRELATIONAL STUDY BETWEEN ORGANIZATION CULTURE, INTERPERSONAL COMMUNICATION, WORK MOTIVATION, AND JOB SATISFACTION OF EMPLOYEE OF FACULTY OF ENGINEERING SAM RATULANGI UNIVERSITY MANADO - Jansen, Freddy (TEKNO, 2010)
The study investigated the relationship between organization culture, interpersonal communication, workmotivation and job satisfaction of employee. The data was gathered from faculty of engineering Sam RatulangiUniversity with n = 40 selected randomly.Result indicated that there were positive correlation between: (1) Organization Culture and Job Satisfaction,(2) Interpersonal Communication and Job Satisfaction, (3) Work Motivation and Job Satisfaction, (4) OrganizationCulture, Interpersonal Communication, and Work Motivation with job satisfaction of employee.Based on the result of the study, the job satisfaction can be improved through organization culture,interpersonal communication, and work motivation.Keyword: Organization Culture, Interpersonal Communication, Work Motivation, Job Satisfaction of Employee